Minimal Wave Speed in a Predator-Prey System with Distributed Time Delay - Fuzhen Wu; Dongfeng Li (Discrete Dynamics in Nature and Society)
This paper is concerned with the minimal wave speed of traveling wave solutions in a predator-prey system with distributed time delay, which does not satisfy comparison principle due to delayed intraspecific terms. By constructing upper and lower solutions, we obtain the existence of traveling wave solutions when the wave speed is the minimal wave speed. Our results complete the known conclusions and show the precisely asymptotic behavior of traveling wave solutions.